Fractional order PID controller design of a DC-DC multilevel boost converter using the Nelder-Mead optimization - Tahri, Ghrissi; Tahri, Fatima; Tahri, Ali (Institute of Advanced Engineering and Science, 2024)
This paper aims to present and analyze the fractional order proportional-integral-derivative (FOPID) control technique of the DC-DC two-level boost converter. The state-space averaged (SSA) method is used to build a small-signal converter mathematical model, which is a crucial task for the control design. A FOPID controller based on the Nelder-Mead optimization algorithm and an artificial intelligence strategy based on a fuzzy logic controller (FLC) are both designed for the voltage mode control (VMC) approach and operate on the continuous conduction mode (CCM). Various step changes in the input voltage amplitude and output load are applied to analyze the performance of the proposed control techniques. In addition, detailed simulation results using the MATLAB-Simulink system are extensively discussed.